L'eau et le développement durable : un couple en rupture sans gouvernance sociétale et coopération décentralisée - Bernard Guesnier (Développement Durable et Territoires)
Hydrological cycle should be treated as a whole by societal governance, probably the only way which could guarantee the future of the couple water-sustainable development, with the participation of governments and citizens. If challenge is global, pertinent actions are local and far from expensive operations. The application of subsidiary principle permits intervention of local communities with participation of populations next to resolve problems of local management.Decentralized cooperation between a number of territorial participants is an opportunity for transfer of financial or material assistance, but also to facilitate transfer know-how, organizational innovation to produce and protect water